1996
DOI: 10.1161/01.cir.94.3.384
|View full text |Cite
|
Sign up to set email alerts
|

Site-Dependent Intra-Atrial Conduction Delay

Abstract: The existence of site-dependent intra-atrial conduction delays and site-dependent dispersion of refractoriness appears to be a common property of the atrial myocardium and does not necessarily forecast AF inducibility. However, the presence of nonuniform anisotropic characteristics of the posterior triangle of Koch may be critical for AF induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Large atria and small reentrant circuits (short wavelength due to a short atrial refractory period and/or slow conduction velocity) allow multiple reentrant circuits to form and increase the probability of sustaining AF, while small atria (or surgically partitioned atria as in the maze procedure) and large reentrant circuits (long wavelengths) are unlikely to be able to sustain reentry and AF. 4 These observations also complement experimental human studies which have demonstrated increased rates of AF in patients with enlarged left atria 17 , intra-atrial conduction defects, [18][19][20] or abnormal atrial refractory periods. 18,20,21 Recent experimental data have suggested, however, that although functional reentry may be of critical importance in initiating and sustaining AF, it is significantly more complex than can be accounted for by only leading circle reentry with multiple simultaneous wavelets.…”
Section: Functional Reentry and The Leading Circle Modelsupporting
confidence: 76%
“…Large atria and small reentrant circuits (short wavelength due to a short atrial refractory period and/or slow conduction velocity) allow multiple reentrant circuits to form and increase the probability of sustaining AF, while small atria (or surgically partitioned atria as in the maze procedure) and large reentrant circuits (long wavelengths) are unlikely to be able to sustain reentry and AF. 4 These observations also complement experimental human studies which have demonstrated increased rates of AF in patients with enlarged left atria 17 , intra-atrial conduction defects, [18][19][20] or abnormal atrial refractory periods. 18,20,21 Recent experimental data have suggested, however, that although functional reentry may be of critical importance in initiating and sustaining AF, it is significantly more complex than can be accounted for by only leading circle reentry with multiple simultaneous wavelets.…”
Section: Functional Reentry and The Leading Circle Modelsupporting
confidence: 76%
“…The relative spatial distributions of atrial rate maladaptation and remodeling 4 may increase APD dispersion to facilitate the transition to and maintenance of AF. These spatially nonuniform repolarization dynamics may help to explain why repolarization sequence is less responsive to activation sequence in the atrium 9,11,24 than the ventricle. 25 Although we studied APD during Afl, the majority of prior studies have been made after electrical cardioversion from tachycardia, 8,15,17,24 meaning that those APDs were often measured at slower (nontachycardia) rates and may also have been influenced by the electrical shock.…”
Section: Nonuniformity and Rate Maladaptation Of Atrial Apdmentioning
confidence: 99%
“…Evidence suggesting that alternate and multiple sites of atrial pacing may result in less site-dependent conduction delay 16 and AF 17 has stimulated the development of pacing techniques for the prevention of atrial arrhythmias. 18 The effects of alternate and multiple pacing sites on atrial mechanical function are unknown.…”
Section: Effect Of Pacing Sitementioning
confidence: 99%